Automated, Low‐Power Chamber System for Measuring Nitrous Oxide Emissions. Issue 2 (1st March 2013) - Fassbinder, Joel J.; Schultz, Natalie M.; Baker, John M.; Griffis, Timothy J.
Abstract : Continuous measurement of soil N2 O emissions is needed to constrain N2 O budget and emission factors. Here, we describe the performance of a low‐power Teledyne N2 O analyzer and automated chamber system, powered by wind and solar, that can continuously measure soil N2 O emissions. Laboratory testing of the analyzer revealed significant temperature sensitivity, causing zero drift of −10.6 nmol mol −1 °C −1 . However, temperature‐induced span drift was negligible, so the associated error in flux measurement for a typical chamber sampling period was on the order of 0.016 nmol m −2 s −2 . The 1‐Hz precision of the analyzer over a 10‐min averaging interval, after wavelet decomposition, was 1.5 nmol mol −1, equal to that of a tunable diode laser N2 O analyzer. The solar/wind hybrid power system performed well during summer, but system failures increased in frequency in spring and fall, usually at night. Although increased battery storage capacity would decrease down time, supplemental power from additional sources may be needed to continuously run the system during spring and fall. The hourly flux data were numerically subsampled at weekly intervals to assess the accuracy of integrated estimates derived from manually sampling static chambers. Weekly sampling was simulated for each of the five weekdays and for various times during each day. For each weekday, the cumulative N emissions estimate using only morning measurements was similar (within 15%) to the estimate using only afternoon measurements. Often, weekly sampling partially or completely missed large episodic N2 O emissions that continuous automated chamber measurements captured, causing weekly measurements to underestimate cumulative N emissions for 9 of the 10 sampling scenarios.